Cuscus (Phalangeridae) Hunting by Biak Ethnic Group in Surrounding North Biak Strict Nature Reserve, Papua - FREDDY PATTISELANNO; JOHAN FREDRIK KOIBUR (Bogor Agricultural University, Indonesia, 2008)
Study on cuscus hunting as a form of wildlife utilization by Biak ethnic group surrounding the North Biak Strict Nature Reserce (CABU) was carried out through direct observation and interview with hunter respondents and other key respondents among four villages that purposively chosen i.e. Inswambesi, Kayomi, Wasani, dan Sansundi at the Warsa District of Biak Numfor, Papua. Two species of cuscus occurs in the study site were common cuscus (Phalanger orientalis) and spotted cuscus (Spilocuscus maculatus) and they were observed as hunting target in CABU. Hunting was performed partly as routine activity used various traditional tools (slash blade, trap, spear, and calling cuscus) and modern weapon (firearm). Cuscus hunting was done to supply animal protein for households, inspite some hunting results raised for consumption and market purposes. For one period of hunting 3-4 cuscus were caught and it was lower than five years ago. It was indicated that the population condition was vulnerable on overharvest and at the present time cuscus population tend to decreased. Traditional wisdom of Biak ethnic group should be explored and practiced again as the form of local law in order to manage cuscus hunting for the future cuscus conservation program. Key words: cuscus, hunting, biak ethnic group